Asset-backed securities in Indonesia: A strategic alternative for infrastructure financing - Prajaningtyas, Winda; Dinarjito, Agung (Badan Pemeriksa Keuangan Republik Indonesia, 2025)
Budget constraints continue to hinder the Indonesian government’s ability to maximize infrastructure development. In order to address these limitations, innovative financing methods are essential for accelerating infrastructure projects with restricted resources. This study explores the potential and challenges of implementing asset-backed securities (ABS) as an alternative financing mechanism for infrastructure development in Indonesia. Employing a qualitative research approach, this study utilizes primary data from interviews and secondary data from financial statements, prospectuses, and previous research on infrastructure asset securitization. The findings indicate that although ABS can serve as a viable alternative financing method for infrastructure development, its implementation presents several challenges. This study aims to contribute valuable insights for regulators, originators, and investors to facilitate the more effective adoption of asset securitization in Indonesia.